Fast Li Ion Dynamics in the Solid Electrolyte Li7P3S11 as Probed by 6, 7Li NMR Spin‐Lattice Relaxation. Issue 12 (16th July 2015) - Wohlmuth, Dominik; Epp, Viktor; Wilkening, Martin
Abstract The development of safe and long‐lasting all‐solid‐state batteries with high energy density requires a thorough characterization of ion dynamics in solid electrolytes. Commonly, conductivity spectroscopy is used to study ion transport; much less frequently, however, atomic‐scale methods such as nuclear magnetic resonance (NMR) are employed. Here, we studied long‐range as well as short‐range Li ion dynamics in the glass‐ceramic Li7P3S11. Li+ diffusivity was probed by using a combination of different NMR techniques; the results are compared with those obtained from electrical conductivity measurements. Our NMR relaxometry data clearly reveal a very high Li+ diffusivity, which is reflected in a so‐called diffusion‐induced 6Li NMR spin‐lattice relaxation peak showing up at temperatures as low as 313 K. At this temperature, the mean residence time between two successful Li jumps is in the order of 3×108 s−1, which corresponds to a Li+ ion conductivity in the order of 10−4 to 10−3 S cm−1. Such a value is in perfect agreement with expectations for the crystalline but metastable glass ceramic Li7P3S11. In contrast to conductivity measurements, NMR analysis reveals a range of activation energies with values ranging from 0.17 to 0.26 eV, characterizing Li diffusivity in the bulk. In our case, through‐going Li ion transport, when probed by using macroscopic conductivity spectroscopy, however, seems to be influenced by blocking grain boundaries including, for example, amorphous regions surrounding the Li7P3S11 crystallites. As a result of this, long‐range ion transport as seen by impedance spectroscopy is governed by an activation energy of approximately 0.38 eV. The findings emphasize how surface and grain boundary effects can drastically affect long‐range ionic conduction. If we are to succeed in solid‐state battery technology, such effects have to be brought under control by, for example, sophisticated densification or through the preparation of samples that are free of any amorphous regions that block fast ion transport.